2005
DOI: 10.1111/j.1708-8208.2005.tb00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Implants in the Severely Resorbed Maxilla: A 2‐Year Retrospective Clinical Study

Abstract: This study demonstrates that the use of short implants may be considered for prosthetic rehabilitation of the severely resorbed maxilla as an alternative to more complicated surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
176
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(191 citation statements)
references
References 16 publications
10
176
3
2
Order By: Relevance
“…35,36 and biomechanical 15 studies have shown that the predictability of short implants is comparable with that of implants of normal length. In the present study, the success rate of short implants was found to be statistically the same as that of longer implants, as reported in another published assessment.…”
Section: Discussionmentioning
confidence: 98%
“…35,36 and biomechanical 15 studies have shown that the predictability of short implants is comparable with that of implants of normal length. In the present study, the success rate of short implants was found to be statistically the same as that of longer implants, as reported in another published assessment.…”
Section: Discussionmentioning
confidence: 98%
“…Such uncertainty is revealed by the various dimensions considered in scientific studies: implants varying from 4 to 10 mm in length. According to Renouard and Nisand, 14 the most appropriate definition of a short implant is a system of which intraosseous length is less than or equal to 8 mm, which therefore can be influenced by the surgical technique. 4,15 Santiago Júnior et al 1 claim that short implants are those implants with less than 10 mm in length.…”
Section: Short Implantsmentioning
confidence: 99%
“…Nowadays, the treatment planning of implant-prosthetic rehabilitation in the atrophic rear maxilla offers vari-ous possibilities linked to the choice of using short (6) rather than angled implants, or enhance the amount of residual bone with techniques to increase the sinus floor (7). In attempt to avoid a bone graft procedure, the choice to insert short implants often is the result of compromised biomechanical situations, in which implants are located in poor bone sites with low quality and high strength of occlusal loading (8-10); short implants have been associated with lower success rates compared with most of standard length implants (11). Currently, in absence of an adequate bone height, the results obtained by the use of short implants may be comparable to those of longer ones placed in regenerated bone, (6) but further investigations are needed to confirm the long-term follow-up data at 5 months published to date.…”
Section: Introductionmentioning
confidence: 99%